The Art of Puppetery in Demak: History of Islamic Da'wah and Lakon Carangan Created by Sunan Kalijaga - Bagaskara, Akbar; Rokhani, Umilia; Jati, Galih Pangestu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The purpose of this article is to analyze in general the phenomenon of puppetry in Demak Regency and its relation to Lakon Carangan created by Sunan Kalijaga as a medium for Islamic preaching. The research method used in this research is a qualitative type with a triangulation validation technique. The results of this research show that Sunan Kalijaga's Lakon Carangan is not just an ordinary story, but a story that is thick with Islamic elements that have been adjusted, as a means of moral and spiritual education that reinforces Javanese Islamic identity. Therefore, the art of puppetry in Demak Regency in the modern era can indirectly contribute to the preservation and sustainable development of Islam in the community